Pengaruh Risk Profile, Earnings, dan Capital terhadap Profitabilitas Perbankan di BEI Tahun 2016-2018 - Yunita, Gusti Agung Putu Dian; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 30 No 8 (2020), 2020)
Banks as financial intermediaries are important financial institutions for economic activities in a country. It is important for banks to have good financial performance. Bank performance is reflected in each banks financial statements or published banking reports, taking into account the banks profitability. The purpose of this study was to determine the effect of loan to deposit ratio (LDR), non performing loan (NPL), operational efficiency ratio, net interest margin (NIM), and capital adequacy ratio (CAR). This research was conducted at the Foreign Exchange National Private Commercial Bank listed on the Indonesia Stock Exchange in 2016-2018. Sample taken were 22 companies with a total of 66 research sample, through non-probability methods with purposive sampling technique. The analysis technique used in this research is multiple linear regression. The results shows that LDR and NPL did not affect on profitability. While operational efficiency ratio, NIM, and CAR significant affect on the profitability. Keywords: LDR; NPL; Operational Efficiency Ratio; NIM; CAR.